(untitled) (College of Basic Education Research Journal, 2026)
The development taking place in the sport of gymnastics is the result of the progress made at the technical and research levels, which helped athletes perform difficult and complex skills, and since the various gymnastics equipment requires most of their skills to be complex, such as rotations, swings, jumps, and flips, this is done by highlighting the ideal performance through modern technology in seeing the ideal performance with the least possible effort or setting a training reserve according to the movement that any player will learn. The research aimed to identify some of the biomechanical variables of the forward hand jump movement by landing. Doubles, singles, and identifying the best movement performed by the research sample according to the effort expended and the correspondence between the opinion of experts in the field of gymnastics effectiveness and the opinion of the analyst in terms of the biomechanical point of view using the Automatlab program. The question that comes to researchers is that if the researchers are unable to seek the help of experts or specialists at the time specified by the researcher in order to photograph his sample during performance or to measure the best motor performance in order to achieve the goals of his research, for example, for comparison or to study the accuracy of performance in any other individual activity, does the time of the main experiment be postponed? The research sample consisted of one player who was chosen intentionally, and he represents one of the Iraqi champions in the gymnastics event for the advanced category. The researchers followed the descriptive approach for its suitability and the nature of the research, as measurement and technical scientific observation were used as means of collecting information. After presenting and analyzing the results, the researchers concluded that the best performance of the research sample in the front hands double landing jump was the first attempt. The best motor performance of the research sample in the forward hand jump with a single landing was the second attempt, and the choice of the best performance by the experts matched the best performance chosen by the analyst according to the point of view of the biomechanical motor analysis, which reduces the researcher’s need to accompany the specialists to the place where the experiment is conducted and also reduces the burden on the experts of coming to the place at the time specified by the researcher. The researchers recommended adopting the results of the biomechanical variables for the best performance chosen by the analyst according to the point of view of the biomechanical motor analysis. Any researcher in the future can When studying any individual activity, he must rely on motor analysis using modern techniques used in research to determine the best motor performance without having to bear the hassle of accompanying specialists or making them bear the trouble to the place where the test is conducted. The study aimed to: - Identify some of the biomechanical variables of the forward hand jump movement in double and individual landings. - Identify the best movement performed by the research sample according to the effort expended. - Matching the opinion of experts in the field of gymnastics effectiveness with the opinion of the analyst in terms of the biomechanical aspect using the Automatlab program. The sample of the study was the champion of Nineveh Governorate in the gymnastics event, the advanced category.